Enhanced passive safety surveillance of standard-dose and high-dose influenza vaccines in Finland and Germany 2023–24 season - Marina Amaral de Avila Machado; Sophie Gallo; Alexander Goldstein; Parth Vachhani; Reddappa Maniganahally Byrareddy; Anu Kantele; Hanna Välimaa; Jörg Schelling (Human Vaccines & Immunotherapeutics)
Enhanced Passive Safety Surveillance was used to detect safety signals before the peak period of immunization with quadrivalent inactivated influenza vaccines (IIV4) in Finland (standard dose [SD]) and Germany (high dose [HD]) in the 2023–24 season. The primary objective was to evaluate adverse drug reactions (ADRs) occurring ≤7 days following IIV4 vaccination. Enrolled participants were vaccinated in routine clinical care settings and encouraged to report ADRs. Exposure data and ADR reports were collected in a near real-time manner using an electronic system. Vaccinee reporting rate (RR) with 95% confidence interval (CI) was calculated as the number of vaccinees reporting ≥ 1 ADR divided by total number of vaccinees. In Finland for SD-IIV4, among 1,003 vaccinees aged ≥ 6 months, 81 reported a total of 192 suspected ADRs occurring ≤ 7 days following vaccination (vaccinee RR 8.08%; 95% CI 6.46, 9.94). In Germany for HD-IIV4, among 1,075 vaccinees aged ≥ 60 years, 15 reported 46 ADRs that occurred in ≤ 7 days of vaccination (vaccinee RR 1.40%; 95% CI 0.78, 2.29). No safety signal was detected during this surveillance. The 2023–24 season surveillance did not suggest any clinically significant changes in safety profile compared with previously reported safety data for SD-IIV4 and HD-IIV4.